2006
DOI: 10.1590/s0103-21002006000200011
|View full text |Cite
|
Sign up to set email alerts
|

Prevenção da reincidência de gravidez em adolescentes: efeitos de um Programa de Planejamento Familiar

Abstract: OBJETIVO: avaliar os efeitos de um programa educativo e assistencial frente a reincidência de gestação em adolescentes. MÉTODOS: estudo descritivo e retrospectivo, realizado no setor de Planejamento Familiar da Universidade Federal de São Paulo a partir de dados coletados em 264 prontuários de adolescentes que tinham como antecedente ao menos uma gravidez anterior a matrícula. RESULTADOS: os dados revelam que a menarca ocorreu, em média, aos 12,2 anos, a sexarca aos 15 e a primeira gravidez um ano após. Ao se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
38

Year Published

2010
2010
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 3 publications
(2 reference statements)
0
11
0
38
Order By: Relevance
“…Several authors have reported the phenomenon of the increasing number of adolescents who start their sexual life early combined with their lack of knowledge about contraception and reproduction (6,10) . We must also consider the implications and impact of such early sexual initiation, often aggravated by lack of knowledge, reflection, and critical awareness of their behavior related to sex.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have reported the phenomenon of the increasing number of adolescents who start their sexual life early combined with their lack of knowledge about contraception and reproduction (6,10) . We must also consider the implications and impact of such early sexual initiation, often aggravated by lack of knowledge, reflection, and critical awareness of their behavior related to sex.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of these factors, unexpected pregnancy has been reported as a vulnerability in this phase of life (3,9,11) , and it may contribute to maternal and neonatal morbidity and mortality, along with birth complications, prematurity, and increased risk of miscarriage (12,13) . Another consequence of adolescent pregnancy is the dropout rate, which can reduce the opportunities for professional growth and development (6) . Therefore, there is need for initiatives that address contraception/family planning involving this population with the purpose of providing counseling to adolescents towards a healthy sexuality with fewer risks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berlofi et al 22 avaliaram os efeitos de um programa educativo e assistencial frente à reincidência de gestação em adolescentes e concluíram que é importante a implementação de programas de planejamento familiar que englobem a educação sexual e a assistência à saúde com oferta do método contraceptivo, voltados a adolescentes.…”
Section: Discussionunclassified
“…11 Diversas políticas e intervenções têm sido propostas e executadas em vários países no sentido de reverter essa realidade de gravidez indesejada na adolescência. [12][13][14][15][16][17][18][19][20][21][22] No entanto, o aumento da taxa de fecundidade entre adolescentes e jovens, assim como o número de óbitos maternos nessa faixa etária, 2,23 evidenciam a necessidade de adequação de políticas de contracepção, planejamento familiar e atenção pré-natal.…”
Section: Introductionunclassified